Does pharmaceutical price regulation affect the adoption of generic competition? Evidence from the OECD, 1999-2008 - Nebibe Varol; Joan Costa-Font; Alistair McGuire (Center for Economic Studies and ifo Institute (CESifo), 2011)
Generic competition in the pharmaceutical market is an effective cost-containment mechanism that improves static efficiency and stimulates pharmaceutical innovation. There is no prior study that has empirically analysed the relative delays in adoption of generic competition. This paper aims to investigate how price regulations in the OECD affect the adoption of generic competition following the first global generic launch of each molecule. Drawing upon data from 1999 to 2008, we estimate the impact of ex-ante price and market size expectations on the probability of generic launch using discrete-time duration modelling with cloglog and logit regressions. The econometric strategy employs both parametric and non-parametric duration dependence and includes controls for generic competition in each country, firm characteristics and molecule heterogeneity. Ex-ante profit expectations result in faster adoption; both expected price and market size increase the probability of launch. Our findings suggest that neither molecule nor firm characteristics have a significant effect on generic adoption across different specifications. Instead, evidence indicates that generic competitors follow a locally oriented strategy in contrast to research-intensive pharmaceutical firms.
Keywords: I11; L51; 330; generic competition; regulation; adoption; discrete-time duration analysis; Generika; Innovationswettbewerb; Arzneimittelmarkt; Staatliche Preispolitik; Wirkungsanalyse; OECD-Staaten